E-learning effectiveness during COVID-19 Pandemic among degree students at UiTM Kampus Seremban 3, Negeri Sembilan / Ilman Hakim Abdullah - Abdullah, Ilman Hakim (2022)
The purpose of this paper is to investigate the E-Learning Effectiveness During COVID-19. Pandemic Among Degree Students at UiTM Kampus Seremban 3, Negeri Sembilan. The participants in this study are degree students. To collect data for the study, researchers utilized an online structured questionnaire to collect 348 responses from students. Researchers have also used quantitative methods to analyze data. The research aims to determine the relationship between ICT, motivation, and virtual competence to student e-learning effectiveness. According to the findings, a constructive connection exists between e-learning effectiveness and ICT, motivation, and virtual competence. In this study, researchers have prepared some limitations for future research.